Factors affecting online shopping behavior of Turkish consumers - Turan, Tunca. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Online shopping have became a new way of purchasing in the last decade in addition to the traditional shopping methods. The growing pattern of online shopping forced managers to direct their resources for developing their online facilities in order to use this huge potential efficiently. Many researches were done for providing guidance to the managers in this new model of doing business. It was found in many studies that since the consumer is at the heart of the online shopping, predicting his/her behavior would be very important to develop online shopping. While doing this, the researchers mostly dealt with the online shopping behavior of the consumer from one perspective, instead of a multiview approach. The aim of this study is to determine the factors which affect online shopping behavior of Turkish consumer in a versatile manner. Since, the electronic equipment and devices (computers, computer hardware and accessories, DVD,VCD, Mp3 players, printers, DVD players, cell phones etc…) constitute a huge portion of total online purchases in the world and in Turkey, the study focuses on electronic equipment and devices. The findings show that online shopping behavior of Turkish consumer on electronic equipment and devices is determined by a combination of Consumer-Related, Web and Web Site Related and Web Vendor Related factors. By taking these factors into consideration together, the managers may predict online shopping behavior of Turkish consumer and develop online shopping in Turkey.
Keywords: Consumer behavior -- Turkey; Internet marketing -- Turkey.